Evaluation Study of the Quality of Performance to Teach the Physical Education Departments and Sports Sciences in Basic Education Colleges for their Teaching Tasks According to Edward Deming's Standards - Salam Hantosh Rashed (Journal of Global Pharma Technology, 2018)
The current research dealt with the importance of performance in teaching physical education and sports sciences to what the university education institutions consider the highest educational summit in all countries of the world, and this is especially important because it is considered the highest educational and educational value in the pyramid of learning from kindergartens to university education. The current research problem is highlighted in the availability of quality standards in the teaching of Physical Education and Sports Sciences. The aim of this research is to determine the list of criteria for evaluating the performance of the Physical Education and Sports Sciences. The researchers used the descriptive approach as the most suitable for the study in the light of the research objectives. The results reached recommendations such as raising the level of training by the university or college by engaging them in courses and development programs for teaching performance. And the need to adopt the section of the comprehensive quality standards for all subjects. And the establishment of awards and rewarding encouragement for teachers outstanding and distinguished in the development of their performance in the light of quality standards and university accreditation.Keywords: Evaluation study, Physical education, Teaching tasks and Edward Deming's standards.